High incidence of osteochondral lesions after open reduction and internal fixation of displaced ankle fractures: Medium-term follow-up of 100 cases. Issue 3 (March 2016) - Regier, Marc; Petersen, Jan Philipp; Hamurcu, Ahmet; Vettorazzi, Eik; Behzadi, Cyrus; Hoffmann, Michael; Großterlinden, Lars G.; Fensky, Florian; Klatte, Till Orla; Weiser, Lukas; Rueger, Johannes M.; Spiro, Alexander S.
Abstract: Background: The incidence of osteochondral lesions (OCLs) in association with displaced ankle fractures has only been examined in two previous studies. In both studies magnetic resonance imaging (MRI) was performed prior to open reduction and internal fixation (ORIF). Because MRI may overdiagnose or overestimate the extent of OCLs in an acute trauma setting the aim of this study was to determine the incidence of OCLs after ORIF of displaced ankle fractures using MRI at medium-term follow-up, and to analyse if the severity of fracture or the clinical outcome correlates with the incidence of OCLs. Patients and methods: Following institutional review board approval a total of 100 patients (mean age, 41.3 years; range, 17.9–64.3 years) with a displaced ankle fracture who had undergone ORIF according to the AO principles were included in this study. The American Orthopaedic Foot and Ankle Society (AOFAS) hindfoot score was used to quantify the clinical outcome and MR images were evaluated for OCLs of the talus and distal tibia after a mean of 34.5 months (range, 17.5–54.1 months). Results: OCLs were found in 40.4% of the patients. Logistic regression revealed a significant correlation between the severity of fracture and the incidence of OCLs. Patients with a trimalleolar fracture ( p = 0.04) or an ankle fracture dislocation ( p = 0.003) had a significantly higher risk for developing an OCL compared to those with a type B fracture. Logistic regression also demonstrated a significant correlation between the clinical outcome (AOFAS score) and the incidence of OCLs ( p = 0.01). The risk for developing an OCL increases up to 5.6% when the AOFAS score decreases by one point. Conclusion: OCLs were frequently found in association with acute ankle fractures at medium-term follow-up, and the severity of fracture was associated with an increased number of OCLs. Considering the disadvantages of MRI including the high cost and limited availability, the results of this study may help to explain why anatomic surgical realignment of displaced ankle fractures may still be associated with poor clinical outcomes.